Evaluasi Kebijakan Pengurangan Penggunaan Kantong Plastik di Pasar Wonokromo Kota Surabaya - Muhammad Bangkit Adi Kusuma; Tauran T; Suci Megawati; Ahmad Nizar Hilmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The problem of plastic waste is becoming an increasingly serious environmental issue in Surabaya, particularly from trading activities in traditional markets. The Surabaya City Government enacted Mayoral Regulation Number 16 of 2022 concerning the Reduction of Plastic Bag Use as an effort to reduce plastic waste and encourage the use of environmentally friendly bags. However, at Wonokromo Market, plastic bag use is still quite high. This study aims to initiate the implementation of this policy at Wonokromo Market in Surabaya City. This study uses a qualitative method with a descriptive approach. Data collection was conducted through observation, interviews, and documentation with informants from the Surabaya City Environmental Agency, market managers, traders, and buyers. Data analysis used the Miles and Huberman model with reference to William N. Dunn's six policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results show that the policy has not been implemented optimally. The use of plastic bags still occurs in sales activities, so effectiveness has not been achieved. In terms of efficiency, socialization and supervision have not been able to significantly reduce plastic use. In terms of adequacy, the policy has not provided a comprehensive and sustainable solution. In terms of equity, the burden of the policy falls more heavily on traders, while buyers have not received equitable information. In terms of responsiveness and accuracy, the policy has not yet aligned with the needs and conditions of traditional markets. Therefore, increased outreach, supervision, and an approach tailored to the market community's needs are needed.